Disputing centralities amidst Covid-19: The triangular relationship of ASEAN, China and Timor-Leste - Seixas, P.; Mendes, N.; Lobner, N.; Lam, K. (The paradox of ASEAN centrality: Timor-Leste betwixt and between, 2023)
As Covid-19 has grown into a pandemic marking 2020, international relations dynamics find themselves steeped in a significant rearrangement of previous power constellations. In this research, we want to explore the building (and reorganization) of regional centrality in the midst of a pandemic crisis, looking at ASEAN and China and their longstanding silent dispute about their geostrategic and international power dynamics (Kuok, 2020). This dispute, as we propose, should be analyzed through Timor-Leste as a middle-ground of negotiation/middleman between global powers, understanding, on the one hand, the small country’s long history with ASEAN while standing on the threshold of the grouping as a member yet to be and, on the other hand, its bilateral relations with China which have been strengthened since Timor-Leste’s independence in 2002